2008
DOI: 10.1038/jes.2008.67
|View full text |Cite
|
Sign up to set email alerts
|

Impact of measurement error on quantifying the importance of proximity to point sources of air pollution

Abstract: This project was motivated by the investigation of the impact of primary oil and gas infrastructure on levels of air pollutants in western Canada. In the published models, we assumed that the distances between sources and air monitors were the key determinants of exposure and were measured precisely. These models related the logarithm of air pollutant concentration to a function of separation distance (''distance weight''). We undertook a simulation study to determine the impact on the observed source-pollutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another limitation is that the present work is based on the assumption that the distances from sources to monitoring stations were determined with negligible error. Previous work [25] showed that if the error was appreciable, then the shape of the association of interest can be distorted and power to detect associations diminished. Although this was shown under different parameterization of separation distance, a similar effect may be expected using our proposed model [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the present work is based on the assumption that the distances from sources to monitoring stations were determined with negligible error. Previous work [25] showed that if the error was appreciable, then the shape of the association of interest can be distorted and power to detect associations diminished. Although this was shown under different parameterization of separation distance, a similar effect may be expected using our proposed model [26].…”
Section: Discussionmentioning
confidence: 99%